EFEKTIFITAS PERANGKAT MODEL PROBLEM BASED LEARNING DENGAN PENDEKATAN MULTIPLE INTELLIGENCES UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH FISIKA PESERTA DIDIK - Ananda Fatara Suwandi; Hairunnisyah Sahidu; I Wayan Gunada (Jurnal Penelitian Pendidikan IPA, 2021)
This research aims to develop problem-based learning model learning tools with multiple intelligences approaches to improve the effective physics problem-solving skills of learners. This research is research and development with 4D models defined, designed, developed, and disseminated. The products developed in the form of syllabus, lesson plan, student worksheet, and instrument tests of learners’ problem-solving and logical-mathematical skills. The validity of the product was assessed by six validators, namely three lecturers and three practitioner teachers with a Likert scale analysis. After the validity test, the learning device was conducted a limited trial that aims to measure the effectiveness of learning devices to get N-gain test scores through questionnaires about the ability to solve problems and mathematical logic of learners and efficiency determined from the response of teachers and learners. The results of the study based on assessments from validators showed the overall device averaged above 3.27 with excellent categories. Then the average result of the N-gain test obtained a value of 0.69 with a moderate category. Based on the results of the analysis of the response of learners to the module showed positive criteria with the acquisition of 66.7%. These results can be concluded that the developed product is effectively used in learning